A Case of Mesenchymal Hamartoma of the Chest Wall in a 4-Month-Old Infant - Lee, Margaret Yee Wah (Am J Case Rep, 2019)
Patient: Male, 4-months Final Diagnosis: Mesenchymal hamartoma Symptoms: Asymptomatic chest wall mass Medication: — Clinical Procedure: — Specialty: Radiology OBJECTIVE: Rare disease BACKGROUND: Mesenchymal hamartoma of the chest wall is a rare benign lesion that typically presents in early infancy. However, the clinical presentation can be atypical, with imaging features that mimic infection or malignancy. Imaging combined with histopathology is essential in the diagnosis. A case of mesenchymal hamartoma of the chest wall in a 4-month-old infant is presented. CASE REPORT: A 4-month-old infant had an incidental finding of a large right-sided chest wall mass. Initial imaging included thoracoabdominal ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI). Histology of an initial open biopsy was inconclusive. The diagnosis of mesenchymal hamartoma was confirmed by histology of the resection specimen, which showed a benign, mixed, chondroid, mesenchymal, and cystic hamartoma with areas of calcification and ossification. CONCLUSIONS: This case showed that the diagnosis of mesenchymal hamartoma of the chest wall, which is characterized by heterogeneous components, may require a combined approach for the diagnosis that includes imaging and histology. Increased clinical awareness of mesenchymal hamartoma in infants may help to guide the approach to the correct diagnosis and prevent unnecessarily radical treatment for this benign condition.